2017
DOI: 10.1136/bjophthalmol-2016-309449
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of chloral hydrate for procedural sedation in paediatric ophthalmology: a systematic review and meta-analysis

Abstract: Despite the paucity of high quality evidence, the existing literature suggests that the use of CH for procedural sedation in children appears to be an effective alternative to general anaesthesia, and it can be safe when administered in the hospital setting with appropriate monitoring and vigilance for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…The systematic review showed that the midazolam oral solution had a lower sedation success rate than chloral hydrate, consistent with the results of the previous systematic review (Mataftsi et al, 2017), but the evidence quality was low, and the chloral hydrate group dose was higher than the regular clinical dose. The overall incidence of adverse effects was comparable.…”
Section: Summary Of Main Findingssupporting
confidence: 85%
See 2 more Smart Citations
“…The systematic review showed that the midazolam oral solution had a lower sedation success rate than chloral hydrate, consistent with the results of the previous systematic review (Mataftsi et al, 2017), but the evidence quality was low, and the chloral hydrate group dose was higher than the regular clinical dose. The overall incidence of adverse effects was comparable.…”
Section: Summary Of Main Findingssupporting
confidence: 85%
“…The UK Formulary recommends taking 0.5 mg/kg of midazolam (maximum dose 20 mg) orally in children 30-60 min before the test (Committee P F., 2017). Seven related systematic reviews were identified (Peng et al, 2014;Sun et al, 2014;Zhang et al, 2014;Guo, 2015;Pasin et al, 2015;Jun et al, 2017;Mataftsi et al, 2017). Midazolam has a lower success rate of sedative hypnosis compared to chloral hydrate, but there is no statistical difference in safety, and the quality of included studies is poor (Mataftsi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly stimulating procedures (e.g., EEG, magnetic resonance imaging, auditory brainstem response) and less stimulating procedures (e.g., computed tomography scan, echocardiogram, and physical exam) would not all be expected to have the same success rate when using an orally administered sedation medication. 16,17 In addition, chloral hydrate is well known for its poor taste and it requires a large volume for sedation (500 mg/5 mL or 250 mg/5 mL), thus causing difficulty in dose administration. Variable gastric absorption also results in unpredictable onset of action and difficulty in ensuring adequate sedation.…”
Section: Discussionmentioning
confidence: 99%
“…The most common adverse effects of chloral hydrate are a paradoxical reaction to sedation, vomiting and respiratory depression. 8 Concerns have been raised about the potential carcinogenic, neurotoxic and neuroapoptotic effects of chloral hydrate, especially when treating children who are younger than three years of age. 9,10 Dexmedetomidine is a novel drug with anxiolytic, sedative and analgesic effects, and it has been shown to diminish the need for other pain medication during medical procedures.…”
mentioning
confidence: 99%